Analysis of Sacharide Monomer and Functional Groups of Fe- Dietary Fiber Complex at Acid Condition Boiling - Leny Yuanita (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
The aim of the study was to describe the changes of sacharide monomer and functional groups of Fe-dietary fiber complex at boiling with acidic medium. The research was designed as the Pre test-Post test Control Group, the treatment of variation pH (pH 3 and 7) and boiling time (raw and 35 minutes). The dependent variables were sacharide monomer of dietary fiber and functional groups of Fe-dietary fiber complex. FeSO4. 7 H2O was added as source of mineral Fe. The results of the study showed: 1) At pH 3-boiling time 35’ treatment, no changes to kinds of dietary fiber sacharide monomer, however changes of monomer content. 2) At pH 3-35’ treatment, the Fe binding both to lignin and cellulose at –OH groups, but it was not able to bind hemicellulose. At raw-pH 7, the Fe binding to lignin at –OH, -COOH groups; to cellulose at –OH, -CH2-O-CH2-, -COO groups; while to hemicellulose at –OH groups.